Spatio-temporal analysis of brand interest using social networks - Lopes-Teixeira, D. (2018)
Social Networks have become part of many people's lives, and applications like Facebook and Twitter are used on a daily basis by millions of users. In such applications, users share their feelings, opinions, and experiences. Twitter in particular, is used to talk about diverse topics, including brands and their products and services. In this paper, we analyze how brand interest is reflected on Twitter and how this platform can be used to monitor mentions of specific brands, as an indicator of brand interest. Our methodology is based on time, location, and the number of brand-related tweets to perform a spatio-temporal analysis. This type of analysis can provide relevant insights into how brand interest evolves over the time and how it might differ from one country to another. We have collected four years' worth of data and report trends, differences, and similarities in terms of brand interest for each brand and for each country.